1987
DOI: 10.1136/hrt.57.1.32
|View full text |Cite
|
Sign up to set email alerts
|

Relation of human cardiac action potential duration to the interval between beats: implications for the validity of rate corrected QT interval (QTc).

Abstract: Fourteen patients undergoing routine cardiac catheterisation were paced at a steady frequency; after this test, stimuli were introduced with a variable preceding interval (test pulse interval). The QT interval of the electrocardiogram and the duration of the monophasic action potential of the right ventricle were measured. QT interval is a function of action potential duration; the two variables were very closely correlated in this study. Both these variables increased in duration with increasing test pulse in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(47 citation statements)
references
References 17 publications
5
42
0
Order By: Relevance
“…Shortening of the QT interval with increased HR is a normal response, 30 but the QT interval is modulated by a number of additional factors [31][32][33] and correction by the Bazett formula might result in some limitations. [34][35][36] Recently, Kligfield et al reported that the QT interval and heart rate (or cycle length) during exercise testing were linearly correlated.…”
Section: Qt Interval and Hr Relation During Exercise In Lqtsmentioning
confidence: 99%
“…Shortening of the QT interval with increased HR is a normal response, 30 but the QT interval is modulated by a number of additional factors [31][32][33] and correction by the Bazett formula might result in some limitations. [34][35][36] Recently, Kligfield et al reported that the QT interval and heart rate (or cycle length) during exercise testing were linearly correlated.…”
Section: Qt Interval and Hr Relation During Exercise In Lqtsmentioning
confidence: 99%
“…36,37 Because it is generally accepted that the QT interval is a function of ventricular APD and that the 2 variables are very closely correlated in humans 38,39 and animals, 40 the combined in vitro and in vivo data from this study provided important clues to the relationship among ion channel block, APD lengthening, and QT interval prolongation. Abnormal QTc interval prolongation is known to predispose to ventricular arrhythmias known as Torsades de Pointes via early afterdepolarization-induced triggered activity.…”
Section: Pathogenesis Of Autoimmune-associated Qtc Prolongationmentioning
confidence: 99%
“…Experiments have shown that QT interval measured on NF RV EGM corresponds to the action potential duration. 13,14 We speculate that the NF EGM performs well because it is more closely associated with local action potential and is less affected by geometric considerations.…”
Section: Comparison Of Intracardiac To Surface Qt Variabilitymentioning
confidence: 99%